Enhance learning through e-portfolio - Anuar Ismail, Mohd Khairul; Wan Razali, Wan Shahida; Awang@Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Mat Jusoh, Nor Asmira; Nik Din, Nik Muniyati (Journal of Islamic, Social, Economics and Development, 2024)
The practice of electronic portfolios has become increasingly popular and adopted not only in higher education and professional training, but also occurs in primary schools. In the Malaysian context, E-Portfolio is seen as a learning support that has the potential to solve ongoing problems for teaching and learning at the higher education level that underlies national policies and agencies. E-Portfolio or electronic portfolio or digital portfolio or web folio or e-folio, is a collection of works in electronic form used by users as a form of record of their progress. This study was conducted with the aim of producing a true understanding of the learning approach through e-portfolio covering the concept, objectives, benefits, challenges and solutions as well as strategies to create a complete portfolio. Library and research methods will be used to gather relevant information and then analyzed using inductive methods to obtain a conclusion. The results of the study found that E-portfolio is a form of assignment that can be given to students in a learning process. This assignment complies with the student-cantered learning approach (PBP) because it involves students actively in the process of acquiring knowledge and skills. Because of that, it is very suitable for use when learning takes place virtually, that is when students and instructors cannot meet face to face. The learning process through e-portfolio is not limited only during the preparation process. Students also learn a lot when the task assessment process takes place through self-assessment and peer assessment.